Mechanistic interaction study of 5,6-Dichloro-2-[2-(pyridin-2-yl)ethyl]isoindoline-1,3-dione with bovine serum albumin by spectroscopic and molecular docking approaches - Mohammed M. Alanazi; Abdulrahman A. Almehizia; Ahmed H. Bakheit; Nawaf A. Alsaif; Hamad M. Alkahtani; Tanveer A. Wani (Saudi Pharmaceutical Journal)
A synthesized and promising biologically hypoglycemic compound 5,6-Dichloro-2-[2-(pyridin-2-yl)ethyl]isoindoline-1,3-dione (5e) was studied for its binding to a model protein (bovine serum albumin; BSA) by spectroscopic and molecular simulation approaches. Fluorescence studies revealed that 5e quenched BSA’s intrinsic fluorescence by static quenching. The experiments were performed at three different temperatures and the quenching constants and binding constants were evaluated. Stern-Volmer constant (Ksv) values decreased from 1.36 × 104 to 1.20 × 104 as the temperature increased suggesting static quenching involvement in the interaction. Decreased binding constants from 1.70 × 104 to 4.57 × 103 at higher temperatures indicated instability of the complex at rising temperatures. Site I (subdomain IIA) of BSA was found to interact with 5e. The thermodynamic results showed the binding interaction was spontaneous and enthalpy driven. The secondary structure alterations in BSA due to interaction with 5e were studied by UV–visible, synchronous fluorescence, and three-dimensional fluorescence spectra. The results indicate the 5e binds effectively to the BSA and thus, this study can be useful in further exploring the pharmacokinetics and pharmacodynamics of 5e. Keywords: BSA, Thermodynamics, Docking, Fluorescence quenching, Spectroscopy